POSSIBILITIES FOR IMPLEMENTING HEALTH-SAVING TECHNOLOGIES FOR PRE-REHABILITATION AND REHABILITATION OF PATIENTS WITH PREDIABETES AND METABOLIC SYNDROME BASED ON HEALTH CENTERS - Лобыкина, Елена Николаевна; Айкина, Татьяна Петровна; Маклакова, Татьяна Петровна; Лютина, Елена Ивановна (Medicine in Kuzbass, 2025)
The successes of modern medicine, the increase in life expectancy, and the recognition of medical rehabilitation as an integral and important part of treatment have led to the intensive development of this industry. Many countries are implementing new approaches to the organization of rehabilitation care, including for people with chronic non-communicable diseases. Among these diseases, special attention is being paid to prediabetes and other metabolic disorders, which are on the rise among the population. Purpose of work is to analyze the system of organizing rehabilitation care (pre-rehabilitation and rehabilitation) for patients with prediabetes and metabolic syndrome in the outpatient (third) stage at the Health Center. Results. The system of medical care for prediabetes requires a comprehensive, multidisciplinary approach that ensures long-term patient compliance with the treatment of prediabetes, which will determine the long-term results of the prevention of type 2 diabetes and comorbid pathology. This approach can be implemented on the basis of Health Centers. The use of the Health Center’s resources, including equipment for assessing functional and adaptive health reserves, and the availability of a multidisciplinary team of specialists (dietitian, medical prevention specialist, psychologist, and physical therapy instructor), combined with a multidisciplinary rehabilitation team and the medical organization’s outpatient medical rehabilitation department’s infrastructure, ensures continuity of care, accessibility, and quality of medical assistance for patients with prediabetes within a three-tier medical rehabilitation system in a single medical facility. Conclusion. Development of the third stage of medical rehabilitation on the meringue of health centersImprove the quality of rehabilitation. The set of medical and rehabilitation tools and experienced specialists will allow for simultaneous correction of concomitant pathology, explanatory work with patients to increase compliance.